Modelling short‐rotation coppice and tree planting for urban carbon management – a citywide analysis. Issue 5 (16th July 2015) - McHugh, Nicola; Edmondson, Jill L.; Gaston, Kevin J.; Leake, Jonathan R.; O'Sullivan, Odhran S.
Summary: The capacity of urban areas to deliver provisioning ecosystem services is commonly overlooked and underutilized. Urban populations have globally increased fivefold since 1950, and they disproportionately consume ecosystem services and contribute to carbon emissions, highlighting the need to increase urban sustainability and reduce environmental impacts of urban dwellers. Here, we investigated the potential for increasing carbon sequestration, and biomass fuel production, by planting trees and short‐rotation coppice (SRC), respectively, in a mid‐sized UK city as a contribution to meeting national commitments to reduce CO2 emissions. Iterative GIS models were developed using high‐resolution spatial data. The models were applied to patches of public and privately owned urban greenspace suitable for planting trees and SRC, across the 73 km 2 area of the city of Leicester. We modelled tree planting with a species mix based on the existing tree populations, and SRC with willow and poplar to calculate biomass production in new trees, and carbon sequestration into harvested biomass over 25 years. An area of 11 km 2 comprising 15% of the city met criteria for tree planting and had the potential over 25 years to sequester 4200 tonnes of carbon above‐ground. Of this area, 5·8 km 2 also met criteria for SRC planting and over the same period this could yield 71 800 tonnes of carbon in harvested biomass. The harvested biomass could supply energy to over 1566 domestic homes or 30 municipal buildings, resulting in avoided carbon emissions of 29 236 tonnes of carbon over 25 years when compared to heating by natural gas. Together with the net carbon sequestration into trees, a total reduction of 33 419 tonnes of carbon in the atmosphere could be achieved in 25 years by combined SRC and tree planting across the city. Synthesis and applications . We demonstrate that urban greenspaces in a typical UK city are underutilized for provisioning ecosystem services by trees and especially SRC, which has high biomass production potential. For urban greenspace management, we recommend that planting SRC in urban areas can contribute to reducing food–fuel conflicts on agricultural land and produce renewable energy sources close to centres of population and demand. Abstract : We demonstrate that urban greenspaces in a typical UK city are underutilized for provisioning ecosystem services by trees and especially SRC, which has high biomass production potential. For urban greenspace management, we recommend that planting SRC in urban areas can contribute to reducing food–fuel conflicts on agricultural land and produce renewable energy sources close to centres of population and demand.